Pengaruh Kepemilikan Manajerial, Profitabilitas, Dan Leverage Terhadap Manajemen Laba Pada Perusahaan Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia (Bei) Periode 2021-2023 - Eka Ermawati; Murfid Mubarok Al Fadhil (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study examines the effects of managerial ownership, profitability, and leverage on earnings management in food and beverage companies listed on the Indonesia Stock Exchange during 2021–2023. Earnings management is concerning because aggressive practices may distort financial reporting, reduce transparency, and damage consumer trust and corporate reputation. Using regression analysis, classical assumption tests confirmed that the data were appropriate for analysis. The partial t-test showed that managerial ownership did not significantly affect earnings management, with a significance value of 0.055. Profitability had a significant effect, indicated by a significance value of 0.000. Leverage had no significant effect, with a significance value of 0.108. The coefficient of determination showed an R-squared value of 0.845, meaning that managerial ownership, profitability, and leverage explained 84.50% of the variation in earnings management, while the remaining 15.50% was explained by other variables outside the model.